Positive and Negative Donor Impurity in an InAs/AlAs Quantum Wire (Journal of Scientific Research, 2010)
Binding energies of positive and negative charged donor impurities in an InAs/AlAs cylindrical quantum wire are investigated. Numerical calculations are performed using the variational procedure within the single band effective mass approximation. We assume that the impurity is located at the axis of the wire. The interband optical transition with and without the exciton is computed as a function of wire radius. The valence-band anisotropy is included in our theoretical model by using different hole masses in different spatial directions. Neutral shallow donors comprise a positively charged donor and a single bound electron. It is observed that (i) negative trions have a higher binding energy than positive trions, (ii) the binding energy of the heavy-hole exciton is much larger than that of the light-hole exciton due to different hole mass values (iii) the exciton binding energy and the interband emission energy are both increased when the radius of the cylindrical quantum wire is decreased and (iv) the effect of exciton influences the interband emission energy. Our results are in good agreement with the recent published results. Keywords: Quantum wire; Impurity level; Binding energy; Excitons. © 2010 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v2i3.4715                 J. Sci. Res. 2 (3), 433-441 (2010)